Social Status of Women Working in the Handicraft Industry (Patan Prospective Journal, 2022)
The labors are the backbone of the industry. The study revealed that the majority of the handicraft working women in Patan industrial Area. This study is based on handicraft industries located on Lalitpur district. The women labors in Handicraft industry, had lack of knowledge, training, education and skill for prestigious job. They are far away from the knowledge of economic rights, women rights and other rights of labors. Some of them were even harassed and abused. Primary as well as secondary data were used in order to explore the status of handicraft working women labors. Out of 112 different industries only 8 handicraft industries were selected. Sample sizes of total 40 women were selected from 8 industries. Therefore total number of sampled workers was 40. There were no special changing rooms or facilities for women workers. The workers had no conscious about labor law but owners had all the ideas to exploit in different aspects. Although there were lots of difficulties for the female workers in Patan industrial estate, handicraft working women were still happy and hopeful that their children will go to school and do a better job in future. They spent some hardly saved money for entertainment, buying new clothes and feasting some days. They faced lots of problem in their day to day life for living. They are struggling for uplifting their social and economic status.